Influence of midwife communication on women's understanding of Down syndrome screening information. (2nd December 2019) - John, Sophie; Kirk, Maggie; Tonkin, Emma; Stuart-Hamilton, Ian
Abstract : Aim: To analyse how midwives communicate Down syndrome screening information and explore whether women's understanding of this information is influenced by midwives' communicative style. Methods: Midwives ( n =16) and women ( n =100) were recruited from a regional NHS unit in the UK. A mixed-methods design encompassed two components; audio-recorded antenatal consultations to assess midwives' communication and quantitative surveys to assess women's understanding. Findings: Midwife communication was not significantly related to women's understanding of Down syndrome screening information. However, qualitative thematic analysis revealed midwife communication was often insufficient in fully describing Down syndrome and screening. Communication was not very interactive, midwives dominated conversations and did not sufficiently check women's knowledge/understanding. Conclusions: Policymakers need to consider these findings. Deficits in midwife communication in relation to established screening practice needs to be addressed through additional training ahead of full implementation of non-invasive prenatal testing into midwifery practice.